Living high and training low - The most effective training regimen for endurance athletes
It is quite common for elite or professional athletes to train at high altitudes (e.g. altitude training camps) with hopes to improve performance during a sea-level competition .This training regimen has proven somewhat effective for those competing in endurance sports. The down side to living and training high is that an athlete must train less rigorously at altitude due to the physiological effects of hypoxia (a deficiency of oxygen reaching the tissues of the body). This is why athletes in training for endurance sports can better improve their performance with a living high and training low regimen. Athletes who live high and train low sleep at high altitude and train at low altitude. Such athletes experience a rise in hematocrit, erythropoietin (EPO) and VO2 max that results from prolonged altitude exposure and are able to maintain a rigorous base level training regimen. Since they are not training at altitude, they do not have to lessen the intensity of training. Research by Benjamin D. Levine and James Stray-Gundersen reveals that these athletes who live high and train low not only experience a greater increase in hematocrit, EPO, VO2 max, but also improve performance during sea level competition 2-3% greater than those athletes who live and train at high altitude. Levine and Stray-Gundersen studied the difference between the following training regimens: 1) live low, train low, 2) live high, train high, and 3) live high, train low. The following chart reflects the results from his study involving 39 runners in a 5,000 m race with finishing times within 80% of the world record. Notice how the the 'live high, train low' regimen produced the greatest increase in performance.